Comparative holistic assessment of using vacuum insulated panels for energy retrofit of office buildings. (15th April 2022) - Alam, Mahmood; Picco, Marco; Resalati, Shahaboddin
Abstract: This research proposes the application of a holistic methodology for the accurate assessment of financial and environmental feasibility of applying thermal insulation materials, including advanced materials such as vacuum insulation panels (VIPs), for energy efficient building retrofit. The methodology is applied to a case study in which different insulation materials, both traditional (Mineral wool; XPS) and advanced insulation (VIPs), are applied as internal insulation to a typical office building requiring retrofit. The building is simulated through dynamic performance simulation under different climate conditions to evaluate its annual energy needs. Financial and energy analysis including embodied carbon are performed using a proposed holistic approach. The financial feasibility highlighted traditional "heating only" approach might be lacking in correctly identifying energy savings, leading to overestimating for traditional materials with payback time as low as 6.4 years for mineral wool. The "holistic approach", accounting for the heating and cooling loads and value of space saved, favours advanced materials such as VIPs as soon as the space reaches high enough value, with payback time between 1.3 and 4.2 years for locations investigated. However, the environmental assessment shows that mineral wool has significantly lower carbon payback time compared to VIPs. For VIPs to be competitive environmentally, lower impact core materials or alternatively higher percentage of recycled/reused fumed silica need to be considered in their production. The holistic methodology presented for the first time allows to consider the implications of embodied carbon of insulation materials used in building retrofitting along with the financial and operational energy considerations. Highlights: Methodology for financial and environmental feasibility of Vacuum Insulation Panels. Dynamic performance simulation of office building retrofit under different climates. Vacuum Insulation Panels are economically feasible in high rental value locations. Higher embodied energy leads to longer carbon payback for Vacuum Insulation Panels. Lower impact core materials to reduce embodied energy of Vacuum Insulation Panels.